The everything art handbook. - Walter Foster (Firm) (Lake Forest, CA Walter Foster Publishing, 2016)
"A comprehensive guide to more than 100 art techniques and tools of the trade."--Front cover.
Keywords: Painting -- Technique -- Handbooks, manuals, etc; Drawing -- Technique -- Handbooks, manuals, etc